Pain, agitation and delirium in the intensive care unit. Issue 12 (December 2021) - McGovern, Christopher; Cowan, Richard; Appleton, Richard; Miles, Barbara
Abstract: Pain, agitation and delirium are common during critical illness and are associated with many adverse consequences. A key aim of critical care is the facilitation of a calm, comfortable patient who can interact with their family and staff. Intensive care unit (ICU) patients frequently have pain from a variety of sources, many of which are not readily appreciated or actively managed. This article explores the challenges of assessing pain in the ICU and outlines methods that can be used to better identify and manage pain in this patient group. Agitation in ICU is often multifactorial, with many of its sources under-recognized. We will discuss the potential reasons that ICU patients become agitated, methods for measuring agitation and the actions that can be taken to alleviate it. Although the use of sedative and anxiolytic drugs is common in the ICU, their use is not without risks. This article will outline these risks, the variety of drugs available and how to use these drugs to a targeted effect. We will also explore delirium, its risk factors, precipitants and associated morbidity and mortality. This article will discuss how to diagnose delirium and the methods used to prevent and manage it.